Optimal Allocation of Fault Current Limiters in Power Systems: A Comprehensive Review - Khalil, Yasser; El Samhay, Adel A.; Elmasry, Said; Shindy, I.M. (Recent Advances in Electrical & Electronic Engineering, 2025)
This paper delves into the potential of Fault Current Limiters (FCLs) as a transformative technology within power systems. FCLs assume a pivotal role in streamlining network expansion efforts, sustaining fault current levels, and augmenting the overall performance of power systems. The classification of FCLs is outlined, encompassing superconducting FCLs (SFCLs), Solid-State FCLs (SFCLs), and non-superconducting FCLs (Non-SFCLs). The core of this study lies in an exhaustive review of relevant literature, with a keen focus on optimal allocation strategies for FCLs. The primary objective of this paper is to function as an all-encompassing reference for both researchers and engineers, providing optimal FCL allocation studies. This paper discusses various techniques for the optimal allocation of FCLs within power systems. These allocation methods are categorized based on multiobjective functions such as cost, fault current reduction, stability, protection coordination, reliability, and power quality. This search presents an overview of the FCL survey structured around key components, including objective functions, design variables, constraints, optimization methods, network types, FCL types, and research contributions. This work aims to empower professionals in the field with a robust understanding of FCL allocation, ultimately contributing to the efficient and sustainable evolution of power systems. FCLs represent a promising technology for enhancing the performance and reliability of power systems, and this paper serves as a comprehensive resource for those interested in optimizing their allocation within these systems.
Keywords: design variables